Abnormal resistive switching in electrodeposited Prussian White thin films - Faita, F. L.; Avila, L. B.; Silva, J. P.B.; Boratto, M. H. [UNESP]; Cid, C.C. Plá; Graeff, C. F.O. [UNESP]; Gomes, M. J.M.; Müller, C. K.; Pasa, A. A. (Elsevier, 2022)
Prussian White (PW) layers were deposited on Au/Cr/Si substrates by electrodeposition and characterized by different techniques. Scanning electron microscopy (SEM) images and Raman mapping reveal a uniform and homogeneous deposit while scanning transmission electron microscopy (STEM) images disclose the grain boundary pattern and the thickness of 300 nm of the PW layer. Resistive switching (RS) effect with an ON/OFF ratio of about 102 was observed. The RS mechanism was investigated from the log-log current-voltage plots. Ionic conduction was observed with an activation energy of 0.4 eV that could be associated with potassium ions as possible charge carriers at the grain boundaries. The endurance characteristics were investigated and a stable abnormal RS was observed for consecutive 500 cycles. Moreover, the retention was also evaluated and the high resistive state (HRS) and low resistive state (LRS) were stable up to 1000 s.
Keywords: Electrodeposition; Prussian White; Resistive switching